Implementasi Model Pembelajaran Team Game Tournament (TGT) Untuk Meningkatkan Hasil Belajar Siswa - Putri, Prihastini Oktasari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
This study aims to: (1) find out how to apply the Team Game Tournament (TGT) type cooperative model in learning mathematics. (2) determine whether using the cooperative model type Team Game Tournament (TGT) can improve student mathematics learning outcomes. The type of research used is Classroom Action Research (CAR). The sample in this study were all grade V students of SD Negeri 1 Plumbon in the academic year 2019/2020 as many as 24 students. The instruments used in this study were observation, documentation and student achievement tests Based on the results of the study, it was concluded that: the use of a cooperative model type Team Game Tournament (TGT) can improve student learning outcomes in mathematics class V SD Negeri 1 Plumbon. This can be shown in the final cycle test results obtained a significant increase in value, meaning that the learning process of mathematics using the cooperative model type Team Game Tournament (TGT), the class average value has increased with the results in the pre-cycle of 51.625; cycle I amounted to 63.75 and cycle II amounted to 75.625. With the percentage of completeness in the pre-cycle of 29.17%, the first cycle of 50% and the second cycle of 79.17%.